Phytochemical screening, antioxidant potential and cytotoxic activity of melastoma malabathricum linn. From different locations - Khamsah Suryati, Mohd; Saravanan, A Dharmaraj; U.S. Mahadeva, Rao (2015)
Objective: The initial study was to screen the phytochemical content of methanol extract of M. malabathricum from seven different locations. The other objective was to evaluate the total phenolic content (TPC), Total flavonoid content (TFC), antioxidant potential and cytotoxic activity (on Hepatoma G2 cells) of these extracts and to determine the relationship between TPC and other parameters.